Controlling rainwater storage as a system: An opportunity to reduce urban flood peaks for rare, long duration storms. (January 2019) - Di Matteo, M.; Liang, R.; Maier, H.R.; Thyer, M.A.; Simpson, A.R.; Dandy, G.C.; Ernst, B.
Abstract: Globally, urban infill is stressing existing stormwater systems, necessitating costly infrastructure upgrades. Although household rainwater tanks provide significant distributed storage, they have virtually no impact on reducing peak flows for rare, long duration events. This study introduces an innovative " smart systems " approach to operating tanks to overcome this limitation. Smart tanks are operated as systems and tank opening/closing is optimised to reduce peak flows. To evaluate the proposed approach, we develop a simulation-optimization model by coupling SWMM with a multi-objective genetic algorithm. The results for a two allotment case study show a consistent reduction in peak flows for a 24 h, 1 in 100-year storm for a range of rainfall patterns and tank sizes. For example, a system of 10 kL smart tanks reduced peak flows by 39%–48% compared with the same sized retention tanks. This smart systems approach provides an opportunity to reduce the cost of stormwater infrastructure. Highlights: We introduce the concept of using systems of smart tanks to reduce peak flows for long duration storms. Real-time operation is used to offset flood peak timing from different sub-catchments. A 2 × 10 kL tank, allotment-scale system reduced peak flows by 39%–48%.